2019
DOI: 10.1002/ijc.32498
|View full text |Cite
|
Sign up to set email alerts
|

Germline variants and somatic mutation signatures of breast cancer across populations of African and European ancestry in the US and Nigeria

Abstract: Somatic mutation signatures may represent footprints of genetic and environmental exposures that cause different cancer. Few studies have comprehensively examined their association with germline variants, and none in an indigenous African population. SomaticSignatures was employed to extract mutation signatures based on whole‐genome or whole‐exome sequencing data from female patients with breast cancer (TCGA, training set, n = 1,011; Nigerian samples, validation set, n = 170), and to estimate contributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Patient cohort, ethics, and pathological assessment. This study was embedded within the Nigerian Breast Cancer Study (NBCS) and approved by the Institutional Review Board of all participating institutions: The University of Chicago, University College Hospital, Ibadan (UCH), and Lagos State University Teaching Hospital (LASUTH) 1,7,9,64 . A grand total of 493 subjects were recruited from UCH (n = 284) and LASUTH (n = 209) between February 2013 and September 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient cohort, ethics, and pathological assessment. This study was embedded within the Nigerian Breast Cancer Study (NBCS) and approved by the Institutional Review Board of all participating institutions: The University of Chicago, University College Hospital, Ibadan (UCH), and Lagos State University Teaching Hospital (LASUTH) 1,7,9,64 . A grand total of 493 subjects were recruited from UCH (n = 284) and LASUTH (n = 209) between February 2013 and September 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of breast cancer genomes reveal population-specific differences in germline predisposition mutation frequency, somatic mutation landscapes, and mutational signatures, mirroring population differences in molecular subtypes [7][8][9][10] . Breast cancer patients of African ancestry demonstrate more TP53 alterations and fewer PIK3CA alterations 6,8 , and Nigerian HR+ /HER2− tumors are characterized by increased homologous recombination deficiency (HRD) signature 8 .…”
mentioning
confidence: 99%
“…In addition to germline variants, somatic variants have been characterised and catalogued in relation to cancer treatment responses. For instance, somatic mutations on EGFR and BCR-ABL genes are highly predictive of gefitinib and imatinib drug response respectively in non-small cell lung cancer patients of European ancestry [ 63 ]. Furthermore, few studies have demonstrated inter-ethnic variability in the frequency of some sensitising somatic variants.…”
Section: Challenges In Genotyping Pharmacogene Variantsmentioning
confidence: 99%
“…Furthermore, few studies have demonstrated inter-ethnic variability in the frequency of some sensitising somatic variants. However, studies on somatic variant profiles in cancer patients in African populations are sparse [ 63 ]. Neoplasms are one of the leading causes of deaths from NCDs in the SSA region [ 12 ].…”
Section: Challenges In Genotyping Pharmacogene Variantsmentioning
confidence: 99%
“…In addition, an association between RDGVs in the DNA glycosylase MBD4 with an increase of C>T mutations at CpG sites was reported 9 , which was also found in several independent studies 47,48 . Furthermore, in a breast-cancer-specific study, the association of RDGVs with APOBEC and deficient homologous recombination (dHR) SNV signatures was investigated across ancestries, without detecting hits significant in both ancestries 49 .…”
Section: Introductionmentioning
confidence: 99%